Extent to Which Crude Protein May Be Reduced in Corn-soybean Meal Broiler Diets Through Amino Acid Supplementation - Si, Jianlin; Burnham, D.J.; Waldroup, P.W. (International Journal of Poultry Science, 2003)
This study was conducted to explore the extent to which CP can be reduced in corn-soybean meal broiler starter diets by amino acid supplementation while maintaining adequate performance. Using corn and soybean meal of known composition, diets were formulated by linear programming using a minimum of 107.5% of NRC (1994) amino acid recommendations. No minimum CP was required; as each amino acid became limiting crystalline sources were provided to meet the minimum specification. In sequence these were Met, Thr, Lys, Val, Ile, Arg, Phe, and Trp, resulting in eight treatments ranging from 16.61 to 22.48% CP. All diets contained 0.3% sodium bicarbonate and 0.2% aluminum hydroxide as a buffer and antacid. Three additional treatments utilized potassium sulfate to maintain a minimum dietary electrolyte balance (Na + K - Cl) of 250 meq/kg. Each treatment was fed to twelve replicate groups of six male broiler chicks from 1 to 21 d. Reducing CP below 20% while providing indispensable amino acids resulted in a significant reduction in body weight (BW) and feed conversion ratio (FCR). Crude protein content of freeze-dried carcasses declined and fat content increased as diet CP decreased. Feather content (actual weight or % of BW) was not affected until the CP was reduced to less than 18%. Maintaining dietary electrolyte balance at 250 meq/kg in reduced CP diets had no significant effect on any parameter.